Molecular Structure and Thermal Stability of Oxide-Supported Phosphotungstic Wells-Dawson Heteropolyacid - Matkovic, Silvana Raquel (2015)
We present, for the first time in literature, a systematic study of the molecular structure of the Wells-Dawson heteropolyacid H6P2W18O62.24H2O (HPA) dispersed on TiO2, SiO2, ZrO2 and Al2O3. The heteropolyacid-based materials were synthesized through a conventional impregnation method (in aqueous and ethanol media) at a loading that corresponds to the theoretical monolayer coverage (dispersion limit loading). The combination of Raman and infrared studies demonstrates the presence of crystals of HPA (regardless of the nature of the medium used during the synthesis) suggesting that the dispersion limit loading was greatly exceeded. In situ temperature programmed analyses demonstrated that the Raman shift of the distinctive W=O Raman mode of the fosfotungstic Wells-Dawson heteropolyacid is sensitive to the local environment, that is the amount of water molecules associated with the structure. Moreover, the aqueous based species associated with such structures are recognizable through infrared spectroscopy.